Risk Management in the Production of Sugar in Mojo Sugar Factory, Sragen Regency - Rizki Musidatun Bakdiyah; Umi Barokah; Mei Tri Sundari (Jurnal Manajemen Indonesia, 2020)
This research aims to determine the risk, kind of risks and formulate the risk handling strategies in the sugar production in Mojo Sugar Factory, Sragen Regency. The analysis method used the variation coefficients (CV) score and Enterprise Risk Management (ERM) approach. The results showed the score of CV is 0.77> 0.5 which means that there is a high risk of sugar production in Mojo Sugar Factory. There are 12 risks identified in this research. The risks with low status are the risk of broken sugar cane and risk of the damaged truck; The risks with medium status miscalculations risk in the yield distribution and the late receipt of funds from PTPN IX. The risk of high status is new tools operation difficulties. The risk of very high status is low sugar cane quality, sugar cane sent to other factories, steam drop, the tools and machines performance stopping while grinding, sugar cane production that is below RKAP, losses, and the total production of sugar that is below the RKAP. The risk management strategies for low-status risks are giving strict punishment to farmers’ partners and more regular and scheduled maintenance. The management strategies for medium status is involving technology in calculating results and implementing wiser based financial management. The management strategy for high-status risk is assisting the operation of new tools by experts. The management strategies for very high status are holding an intensive meeting, conducting education, training programs for employees, benchmarking with other sugar factories which have better performance, make a good relation with the partner. Keywords— Risk; Risk Management; ERM; Risk Analysis; Sugar